THE PARTNERSHIP MANAGEMENT OF PESANTRENS AND COMMUNITIES FOR THE INTEGRATED ECONOMIC AND EDUCATIONAL DEVELOPMENT - Kurniawan, Asep (Pascasarjana IAIN Kudus, 2017)
Pesantrens and communities should be able to establish partnership management for good governance and the common welfare of the economy and education. Recently, many pesantrens, however, are too busy with normative activities than social activities. Similarly, recent society is more individualistic. This situation certainly inhibits this partnership management. For that pesantrens should play their role as institutions of community empowerment aside from being a massage and educational institution. Although, in essence, pesantrens and communities are not separated institutions, because, both of them need each other in achieving the integrated prosperity of economy and education. Thereby, they can make a strong civil society.